State of terror : a novel - Clinton, Hillary Rodham; Penny, Louise (Simon & Schuster and St. Martin's Press, 2021)
A passionate young foreign service officer, a dedicated journalist, and a smart, determined, but as yet untested new secretary of state must team up to defeat an intricate, carefully constructed conspiracy planned to take advantage of four years of an American government out of touch with international affairs.